PENINGKATAN KETERAMPILAN MENULIS ESAI MELALUI MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Olyvia Mustyka (JURNAL PENDIDIKAN ROKANIA, 2016)
The purpose of this study is to describe: (1) Intensifying the process of essay writing skills of students,(2) the result of an increase in student essay writing skills class A Study Program Indonesian Language and Literature STKIP Ahlussunnah Bukittinggi. Data was obtained from qualitative data in the form of sheets observation, field note, questionnaires, and interviews, and quantitative data in the form of test performanc. The findings of a study of the process of improving essay writing skills through cooperative learning model class A student CIRC Language Study Program and Literature Indonesia STKIP Ahl Bukittinggi performing well. The average student test results has increased, averaging at 58.64 prasiklus, in the first cycle 65, and the second cycle 83.37